1999
DOI: 10.1246/bcsj.72.1263
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation, Complexation with Guest Molecules, and Mesomorphism of Amphiphilic Phthalocyanines Having Four- or Eight Tri(ethylene oxide) Chains

Abstract: Zinc and metal-free amphiphilic phthalocyanines (pcs) substituted by four or eight tri(ethylene oxide) chains (3,6,9-trioxadecyloxy groups) {(H2(4EGpc), [Zn(4EGpc)], H2(8EGpc), and [Zn(8EGpc)] in Fig. 1)} have been prepared in order to study their aggregation in water, dioxane, and dioxane/water mixtures, their complexation phenomena with guest molecules in benzene, and mesomorphism in the neat state. In particular, tetra-substituted pcs have C4h symmetry and do not contain other positional isomers. [Zn(8EGpc)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…Very strangely, this D ro mesophase exhibits one more stacking distance h f at 3.48 Å , which is compatible with the face-to-face stacking distance of Pc macrocycles in the D ho mesophase. Although conventional columnar mesophases give only one stacking distance, it was recently reported that two or three stacking distances could be observed in one columnar mesophase [14,15]. These cases are attributable to an equilibrium of dimer monomer or trimer dimer monomer which contains three, two and one times the normal stacking distance h at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…Very strangely, this D ro mesophase exhibits one more stacking distance h f at 3.48 Å , which is compatible with the face-to-face stacking distance of Pc macrocycles in the D ho mesophase. Although conventional columnar mesophases give only one stacking distance, it was recently reported that two or three stacking distances could be observed in one columnar mesophase [14,15]. These cases are attributable to an equilibrium of dimer monomer or trimer dimer monomer which contains three, two and one times the normal stacking distance h at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…Water-soluble phthalocyanines are the most promising photosensitizers for PDT applications [6,7]. However, aggregation (especially in aqueous media) is a very common phenomenon in this family of compounds due to their large p-conjugated systems; this dramatically decreases their fluorescence quantum yields, shortens their triplet state life time and reduces their ability to be used as photosensitizers [8][9][10][11]. In photodynamic therapy, DMSO solutions of phthalocyanines have been also used, because DMSO, with the substance dissolved in it, is able to penetrate directly the tissues and cells, and that is the reason for extraordinary attention given to the absorption and emission properties of phthalocyanines in DMSO solutions [3,12].…”
Section: Introductionmentioning
confidence: 99%
“…Roughly, two distinct kinds of studies can be discerned: (a) the doping of a pure liquid-crystalline donor phase with suitable acceptor dyes and (b) the preparation of mesophases from covalently or non-covalently assembled donor-acceptor complexes. Following the first strategy columnar mesophases of triphenylenes were doped with phthalocyanines [123][124][125][126][127], or 2,4,7-trinitrofluorenone [90,[128][129][130], for example. In these cases efficient quenching of the triphenylene emission was observed as a consequence of energy or charge transfer to the dyes.…”
Section: Mixed Donor-acceptor Systemsmentioning
confidence: 99%